Policy of Innovation in Rewards and Ownership: Support for the development of small and medium-sized enterprises in Slovenia - Avsec, Dejan (Naše gospodarstvo/Our economy, 2013)
The contribution offers support for the development of small and medium-sized enterprises in Slovenia with policies of rewards and ownership using ESOP and USOP methods supportive of social responsibility. Social responsibility depends on owners: If owners and their co-workers are organized and stimulated by ownership in line with ESOP and USOP methods, social responsibility could be realized following the ISO 26000 principles. In Slovenia, ownership transition follows the law on ownership transformation, but in a chaotic rather than planned way and witho- ut ESOP and USOP. The effect was not optimal; in our judgment, ownership was missing. Organizational implementations of ownership would receive support from pooling co-workers' means by 'internal capital accounts' and 'internal social capi- tal accounts' of citizens that would enable capital enlargement. A new model would provide for the rewarding of co-workers (payroll plus variable revenues) and the di- stribution of innovation-based profit in dividends to enterprise owners, which inclu- des everybody under ESOP and USOP. The world faces serious problems of a failing economy and financial crisis. Hence, the renewal of social responsibility based on ESOP and USOP methods is inevitable for promoting ownership-based attitu- de and democratization. Social responsibility is the direction of an ordered world.